2013
DOI: 10.1177/1071100713500653
|View full text |Cite
|
Sign up to set email alerts
|

Ligament Structures in the Tarsal Sinus and Canal

Abstract: The anatomical description provided here may provide a more accurate theoretical foundation for clinical subtalar stability restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 29 publications
4
62
1
Order By: Relevance
“…However, inconsistencies occur in morphologies of ITCL. Cadaver studies have shown that there are two distinct ligaments in the tarsal sinus: ITCL and anterior capsular ligament (ACL) [ 7 , 8 ]. It has been suggested that ITCL and ACL should be considered as two distinct ligaments since they have unique insertion and running patterns.…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistencies occur in morphologies of ITCL. Cadaver studies have shown that there are two distinct ligaments in the tarsal sinus: ITCL and anterior capsular ligament (ACL) [ 7 , 8 ]. It has been suggested that ITCL and ACL should be considered as two distinct ligaments since they have unique insertion and running patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Tochigi et al suggested that the ITCL restrained the subtalar joint in inversion and prevented anteromedial displacement [30].However, several publications questioned the importance of the ITCL [4,6]. For example, Li et al pointed out that the most important ligament of the tarsal sinus was the CL, while the ITCL, although always present, was a thin single-band ligament [31]. Smith and…”
Section: Discussionmentioning
confidence: 99%
“…Its fiber is oriented from the superolateral calcaneal surface to an inferolateral tubercle on the talus neck. Some researchers believed that the CL was more important than the ITCL in stabilizing the subtalar joint [2,3,31]. Earlier studies found that the CL could restrain the inversion and external rotation of the subtalar joint [7,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the anatomy of the ligaments in and around the TSC (Smith, 1958;Cahill, 1965;Schmidt, 1978;Jotoku et al, 2006, Li et al, 2013. None of these studies has quantified the location of the insertions of those ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…For example, on lateral radiographs, the sinus 'opens' or 'closes' from supination to pronation, respectively (Maceira and Monteagudo, 2015). The TSC anatomy has been studied macroscopically (Smith, 1958;Schmidt, 1978;Schwarzenbach et al, 1997;Lektrakul et al, 2001;Rab et al, 2001;Jotoku et al, 2006;Li et al, 2013), microscopically (Rein et al, 2013), and by medical imaging, mostly magnetic resonance imaging (MRI) (Klein and Spreitzer, 1993;Lektrakul et al, 2001;Lee et al, 2008).…”
Section: Introductionmentioning
confidence: 99%